The gentle civilizer of nations : the rise and fall of international law, 1870-1960 - Koskenniemi, Martti (Hersch Lauterpacht memorial lectures., 2002)
Koskenniemi combines legal analysis, historical and political critique and semi-biographical studies to trace the emergence of a liberal sensibility relating to international matters in the late nineteenth century, and its subsequent decline post Second World War. This highly readable and learned study ends with a critique of post-1960 'instrumentalism'.